Private Health Insurance in Ireland A Case Study - Colombo, Francesca (OECD Publishing, 2004)
This paper analyses the Irish private health insurance (PHI) market. It describes how PHI interacts with the public system, and assesses its contribution to equity, efficiency and responsiveness of the health system. The analysis identifies some of the factors affecting insurance market performance and its impact on the health system, including market characteristics, the regulatory and fiscal environment, health system organisation, and any actors' incentives and behaviours. PHI plays a prominent role in Ireland. The health system is designed to offer comprehensive publicly funded health services to low-income groups, and universal public hospital coverage. Policies have encouraged the development of PHI to provide all individuals with a private alternative to the public system, as well as a means of funding cost-sharing and services not covered by the public system. With the implementation of the requirements of the Third EU Non-Life Directive, the PHI market, historically ...
Keywords: Social Issues/Migration/Health; Ireland